EVALUATION OF DRUG USED AND CLINICAL NUTRITION IN STROKE PATIENTS AT TNI AU DR. SALAMUN BANDUNG HOSPITAL - Bahana M R, Irianti
Stroke, which is one of the leading causes of death in Indonesia, still became heavy burden towards public health issue in Indonesia. Stroke is caused by varied etiology and risk faktor that can potentially lead to Drug Related Problems (DRPs). Nutrition aspects became an important factor in the recovery of stroke patients. This is because nutrition aspect play critical part in the management of the common problems that occurs during stroke condition such as dehydration and dysphagia. The objective of this study is to evaluate the use of drug and nutrition in stroke patients, and the mixing techniques before feeding. This study also carried out to evaluate the quality of life or functional independence of stroke patients using Barthel index. Method used in this research is observational with descriptive evaluational design which is done concurrently in TNI AU Dr. Salamun hospital from January until March 2015. Result showed that for the clinical nutrition aspects, the number of calories in food and frequency of feeding in stroke patient is appropriate. However, potassium and calcium amount need to be increased while fiber content should be decreased up to 25%-30% in order to meet daily requirement. For drug used aspect, there are Drug Related Problems (DRPs) which can be categorized mild i.e. untreated indication (26.58%), medication without indication (29.69%), inappropriate dosage (3.12%), major drug interaction (1.56%), and inappropriate drug selection (3.12%). Through Barthel index, the quality of life either ischemic stroke patient (p=0.000) and hemorrhagic stroke patient (p=0.003) are improved very significantly after received hospital standard nutrition and therapy. From those result, it can be concluded that the energy and nutrient requirement of the patient also technique of mixing drug and food is appropriate. However, from the aspect of drug use still requires more frequent communication among doctors, pharmacists, and nutritionists in order to eliminate drug-drug interaction and drug-food interaction that may cause adverse effect. In general, stroke patients who are treated and received standard nutrition in TNI AU Dr. Salamun hospital have an increased quality of life.